PERSISTENCE OF PESTICIDE FORMULATIONS ALONE AND IN COMBINATION WITH FERTILIZERS IN SOIL - Akhtar, Shahida; Hasan, Nusrat; Masud, Syed Zafar (Biological Sciences - PJSIR, 2001)
Experiments were designed to investigate the persistence of the active ingredients in commercial pesticide formulations viz; cypermethrin 10% EC, fenvalerate 20% EC, deltamethrin 25% EC, malathion 25% EC, profenofos 40% EC and chlorfenvinphos 25% EC alone and with various commercial fertilizers viz; urea, DAP (Diammoniurn phosphate) & SOP (Sulphate of potash) in soil. All fertilizers were added @ 1% to soil collected from vegetable growing areas near Karachi with insecticide fortifications @ 100 ppm and 400 ppm. Results indicate that the application of fertilizers with insecticides does affect the persistence of the insecticides to some extent although each insecticide behaved differently. Malathion was most affected by all fertilizers and deltamethrin least affected.